2021
DOI: 10.4103/jcar.jcar_4_21
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human epidermal growth factor receptor 2, Survivin, Enhancer of zeste homolog -2, Cyclooxygenase-2, p53 and p16 molecular markers in Gall bladder carcinoma

Abstract: INTRODUCTION: Gallbladder cancer exhibits striking variability in the global rates, reaching epidemic levels for some regions and ethnicities. The basis of its variability resides in differences in environmental exposure and intrinsic genetic predisposition to carcinogenesis. There is little information present regarding genetic and molecular alterations in gall bladder cancer (GBC). We, therefore, have evaluated the molecular marker expression in GBC and studied their correlation with clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…HER2 is another transmembrane tyrosine kinase receptor protein whose overexpression has been detected and correlated to the progression of several human cancers [63,64]. Overexpression of HER2 in GBC has been demonstrated in several studies [64,65,66] but the frequency of overexpression and gene amplification has been found to be lower than other markers. HER2 protein overexpression in relation to gene amplification is yet to be established in GBC [65].…”
Section: Her2mentioning
confidence: 99%
See 2 more Smart Citations
“…HER2 is another transmembrane tyrosine kinase receptor protein whose overexpression has been detected and correlated to the progression of several human cancers [63,64]. Overexpression of HER2 in GBC has been demonstrated in several studies [64,65,66] but the frequency of overexpression and gene amplification has been found to be lower than other markers. HER2 protein overexpression in relation to gene amplification is yet to be established in GBC [65].…”
Section: Her2mentioning
confidence: 99%
“…HER2 levels reported across different studies conducted on GBC samples exhibit a large variation. These reported variations in HER2 expression have been attributed to the choice of different assays and scoring systems with varying specificity and sensitivity towards GBC [66]. The most commonly used scoring systems in these studies are based on the criteria used for gastric cancer [68] and breast cancer [66] along with the Hercep test scoring system [54].…”
Section: Her2mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The epidermal growth factor receptor family includes HER1 (EGFR), HER-2 (erbB2), HER3 (erbB3), and HER4 (erbB4). 5,6 These RTKs are transmembrane single subunit glycoproteins with intracellular tyrosine kinase, a catalytic domain, an extracellular ligand-binding domain, and a transmembrane domain. HER-2, also known as receptor tyrosine-protein kinase erbB-2, is a member of the EGFR family of receptor tyrosine kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Data on PR immunostaining in the literature typically lacks associations with patient age, gender, or stage in cancer [6][7][8][9][10][11][12][13][14] and is overall highly variable. For example, the reported range of PR positivity ranges from 0 to 76% in colorectal cancer [6][7][8], from 0 to 52% in adenocarcinoma of the gall bladder [9,10,15,16], from 0 to 85% in prostate cancer [11,17,18], from 0 to 63% in non-small-cell lung cancer [12,19,20], from 38.7 to 75.8% in papillary thyroid carcinoma [13,14,[21][22][23][24], and from 15.2 to 100% in angiomyolipoma of the kidney [25][26][27]. These conflicting data are likely to be caused by the use of different antibodies, staining protocols, and interpretation criteria in these studies.…”
Section: Introductionmentioning
confidence: 99%